Waterborne epoxy emulsion modified low linear expansion coefficient repair mortar and preparation method thereof
Patent Information
- Application Number
- CN202611519860.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-29
- Publication Date
- 2026-10-30
AI Technical Summary
但现有商用环氧砂浆存在核心技术缺陷:纯环氧树脂线膨胀系数普遍超过50×10-6/℃,即便掺杂硅微粉、水泥、普通石英砂等常规无机填料改性,固化后环氧砂浆的线膨胀系数仍高于20×10-6/℃
(1)本发明选用纯度≤98%的破碎熔融石英砂,与常规的电子级高纯熔融石英砂(纯度≥99%,价格高昂)相比,该种低纯度破碎熔融石英砂,价格仅为高纯料的20%~30%。且该填料固有线膨胀系数仅0.5×10-6/℃,远低于常规细骨料线膨胀系数的10×10-6/℃,经高比例填充可将环氧砂浆整体线膨胀系数调控至8~12×10-6/℃,与混凝土基材变形特性相匹配,能够有效消除温度变化引发的混凝土-环氧砂浆界面剪切应力,从根源防止修补层在长期温变环境下空鼓、脱落。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of concrete repair materials technology, specifically relating to water-based epoxy emulsion modified low linear expansion coefficient repair mortar and its preparation method. Background Technology
[0002] Epoxy mortar is currently the mainstream material for repairing concrete surface defects. It boasts significant advantages such as high bonding strength, excellent toughness, good impact and abrasion resistance, and high tensile strength, making it widely used in repairing concrete damage, spalling, and cracks in fields such as water conservancy, construction, and transportation. However, existing commercial epoxy mortars suffer from a core technical deficiency: the linear expansion coefficient of pure epoxy resin generally exceeds 50 × 10⁻⁶. -6 Even with modification using conventional inorganic fillers such as silica fume, cement, and ordinary quartz sand, the linear expansion coefficient of the cured epoxy mortar remains higher than 20×10⁻⁶℃. -6 / ℃. The linear expansion coefficient of ordinary concrete substrate is only 8~12×10. -6 The coefficients of linear expansion of the epoxy mortar and concrete differ by more than double at ℃. During alternating temperature changes in the natural environment, the thermal deformation of the epoxy mortar repair layer and the concrete substrate differs greatly, resulting in continuous alternating shear stress at the interface. After long-term service, the interfacial bond strength between the epoxy mortar and concrete continuously weakens, eventually leading to defects such as hollowing, detachment, and cracking of the repair layer. This significantly shortens the service life of the concrete repair structure and results in extremely high maintenance costs.
[0003] Fused silica sand is an ultra-low expansion inorganic filler with a linear expansion coefficient of only 0.5 × 10⁻⁶. -6 The temperature is / ℃, far superior to conventional fillers such as ordinary quartz sand, theoretically significantly reducing the thermal expansion coefficient of epoxy mortar. However, this filler has not been able to be applied on a large scale in the field of epoxy mortar due to two major bottlenecks: First, fused silica sand is prepared by melting, cooling, and pulverizing at temperatures of over 1000 degrees Celsius, resulting in complete dehydration and condensation of surface-active silanol groups, forming highly inert siloxane bonds with low surface free energy and no active polar groups; second, epoxy resin has a large molecular weight, high cohesive energy, and high surface tension, resulting in a large contact angle and poor spreadability when the two are combined, preventing the resin from effectively encapsulating the sand particles. This leads to problems such as poor cohesion, lack of density, and low strength in the prepared mortar. Traditional silane coupling agents (KH-560, KH-550, etc.) cannot achieve a bonding and composite effect on fused silica sand. After hydrolysis, the coupling agent does not have enough silanol groups to complete the anchoring reaction, and can only undergo physical adsorption or self-crosslinking, failing to construct organic-inorganic interfacial chemical bonds. Conventional wetting and dispersing agents can only optimize the thermodynamic contact angle, but cannot solve the kinetic wetting problem of high-viscosity resins, and are prone to foam stabilization and phase separation problems. At the same time, high-purity fused silica sand (purity ≥99%) commonly used in the electronics industry is expensive, with extremely high procurement costs, and is completely unsuitable for mass application scenarios in construction engineering.
[0004] Existing low-expansion epoxy materials have publicly disclosed related technologies, but they generally suffer from problems such as poor matching of expansion coefficients, high cost, weak interfacial bonding, and insufficient engineering applicability. CN101864147A uses a compound epoxy system combined with spherical silica micropowder to prepare a low-expansion filler, with a linear expansion coefficient of 20~40×10. -6 The temperature range is significantly higher than that of concrete substrates, making them prone to interfacial delamination and cracking under temperature fluctuations, thus compromising durability for concrete repair. US5434199A utilizes a high-dosage spherical fused silica filler; the ultrafine powder is easily encapsulated by resin, avoiding poor cohesion and reducing the coefficient of thermal expansion to 12.9 × 10⁻⁶. -6 While the temperature is [temperature value missing], the price of this high-purity spherical filler is high, more than 20 times that of low-purity crushed fused silica sand, resulting in low cost-effectiveness in engineering projects. Therefore, developing a modified epoxy mortar that matches the linear expansion coefficient of concrete, exhibits excellent cohesiveness, low cost, and outstanding durability is a pressing technical problem that needs to be solved in this field. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide waterborne epoxy emulsion modified low linear expansion coefficient repair mortar and its preparation method.
[0006] The objective of this invention is achieved through the following technical solution: The first aspect of this invention is to provide a water-based epoxy emulsion-modified repair mortar with a low coefficient of linear expansion, comprising, by weight, 100 parts of low-purity crushed fused silica sand, 2-10 parts of water-based epoxy emulsion component, and 12-20 parts of oil-based epoxy resin component; wherein the low-purity crushed fused silica sand has a silica purity of 90%-98% and a coefficient of linear expansion of 0.4-0.6 × 10⁻⁶. -6 / ℃. The surface of the low-purity crushed fused silica sand particles is coated with a coating film formed after the water-based epoxy emulsion component has cured.
[0007] The raw materials of the waterborne epoxy emulsion component include: waterborne epoxy emulsion, waterborne curing agent, and water, wherein the mass ratio of the waterborne epoxy emulsion to the waterborne curing agent is 0.2~5:1, and the water is 0.5~2 times the total amount of the waterborne epoxy emulsion and the waterborne curing agent; the bonding strength of the waterborne epoxy emulsion component to the low-purity crushed fused silica sand is ≥2.0MPa, and the bonding test method is as follows: the prepared waterborne epoxy emulsion component is applied to a 20mm fused silica cube, and after the film is dried, a pull-out test is performed according to GB / T16777.
[0008] By weight, the oily epoxy resin component comprises: 100 parts epoxy resin, 10-25 parts epoxy diluent, 0.3-0.6 parts defoamer, and 25-100 parts epoxy curing agent.
[0009] This invention designs a repair mortar with a coefficient of linear expansion close to that of concrete. During preparation, the low-purity crushed fused silica sand is first surface-modified using a water-based epoxy emulsion component, and then compounded with an oil-based epoxy resin component. After modification, the surface of the low-purity crushed fused silica sand particles is coated with a film formed by the curing of the water-based epoxy emulsion component. The repair mortar made using the modified low-purity crushed fused silica sand as filler effectively solves problems such as cracking caused by the mismatch between the coefficient of linear expansion and that of concrete. Specifically, this invention selects crushed fused silica sand with a purity ≤98% as the core filler, whose inherent coefficient of linear expansion is only 0.5 × 10⁻⁶. -6 / ℃, approximately 5% of that of ordinary quartz fillers, with an inherently low coefficient of linear expansion (0.4~0.6×10). -6 The overall linear expansion coefficient of epoxy mortar can be adjusted to 8~12×10 (℃). -6 / ℃, with concrete substrate (8~12×10 -6 The temperature (°C) is perfectly matched, which can eliminate the interfacial shear stress caused by temperature changes and prevent the repair layer from blistering and falling off under long-term temperature change environment.
[0010] However, a major reason why existing technologies struggle to match the linear expansion coefficients of repair mortar and concrete lies in the difficulty of bonding the filler and oil-based epoxy resin components. The conventional approach is to use silane coupling agents to combine the two, but this still results in fluctuations in the linear expansion coefficient due to the trade-off between the two. This invention preferably uses fused silica sand as the filler. However, this type of silica sand also presents a compatibility issue with epoxy resin: after high-temperature preparation, fused silica sand has strong surface inertness, resulting in poor wetting properties with traditional oil-based epoxy resins. Therefore, it is generally not suitable as a filler in epoxy resin repair mortars. To address the aforementioned issues in the compounding of fused silica sand and epoxy resin, this invention proposes to abandon traditional silane coupling agents and design an aqueous epoxy resin emulsion. This emulsion forms a coating film on the outer surface of the fused silica sand. Utilizing the low surface tension and strong penetration characteristics of the aqueous epoxy emulsion, it penetrates into the micropores of the fused silica sand during stirring. After curing, it forms microscopic mechanical interlocking points. Simultaneously, the polar groups of the aqueous epoxy resin generate dipole adsorption with the Si-O-Si bonds on the silica sand surface, constructing a three-dimensional coating structure. This effectively solves the problems of poor wettability and insufficient mortar cohesion in the fused silica sand and epoxy system.
[0011] The low-purity crushed fused silica sand has a particle size of 0.01mm to 2.5mm, and the sand gradation is as follows: 1.25~2.5mm: 5%~15%, 0.63~1.25mm: 20%~40%, 0.315~0.63mm: 20%~40%, 0.16~0.315mm: 10%~30%, and 0.01~0.16mm: 5%~25%. The preferred sand gradation is: 1.25~2.5mm: 10%, 0.63~1.25mm: 30%, 0.315~0.63mm: 30%, 0.16~0.315mm: 20%, and 0.01~0.16mm: 10%. This continuously graded sand has high packing density and low interparticle porosity, which helps reduce epoxy resin filling loss. Higher epoxy resin content leads to greater linear expansion; therefore, controlling the gradation to reduce the resin content in the mortar helps lower the coefficient of linear expansion. Furthermore, it allows the epoxy resin to more effectively coat and bond, while coarse particles provide skeletal support and fine particles fill the gaps. Combined with the characteristics of fused silica sand—numerous edges, rough surface, and high oil absorption—the epoxy resin can form a uniform and robust coating layer on the sand particles, ultimately resulting in epoxy mortar with excellent mechanical properties and good volume stability.
[0012] The aqueous epoxy emulsion has a viscosity of 100-2000 cps at 25°C, a solid content of 35-100 wt%, and an epoxy equivalent of 120-400 g / eq; the aqueous curing agent has a viscosity of 100-2000 cps at 25°C, a solid content of 30-100 wt%, an amine value of 120-250 mg KOH / g, and an active hydrogen equivalent of 70-210 g / eq. Preferably, the aqueous epoxy emulsion HB380 has a viscosity of 1000-2000 cps at 25°C, a solid content of 60 wt%, and an epoxy equivalent of 370 g / eq; the aqueous curing agent HB6610 has a viscosity of 100-200 cps at 25°C, a solid content of 50 wt%, an amine value of 220-250 mg KOH / g, and an active hydrogen equivalent of 190 g / eq. The waterborne epoxy emulsion selected in this invention is a conventionally available waterborne epoxy resin and a matching waterborne curing agent.
[0013] In the oily epoxy resin component, the epoxy resin is one or more of the following: bisphenol F diglycidyl ether with an epoxy equivalent of 155-165 g / eq, bisphenol F diglycidyl ether with an epoxy equivalent of 165-167 g / eq, bisphenol F diglycidyl ether with an epoxy equivalent of 165-175 g / eq, bisphenol A diglycidyl ether with an epoxy equivalent of 165-175 g / eq, bisphenol A diglycidyl ether with an epoxy equivalent of 180-185 g / eq, or bisphenol A diglycidyl ether with an epoxy equivalent of 183-190 g / eq. Preferably, the epoxy resin is one or more of the following: bisphenol F diglycidyl ether EMTE160 with an epoxy equivalent of 155-165 g / eq, bisphenol F diglycidyl ether EMTE170L with an epoxy equivalent of 165-167 g / eq, bisphenol F diglycidyl ether EMTE170 with an epoxy equivalent of 165-175 g / eq, bisphenol A diglycidyl ether EMTE126 with an epoxy equivalent of 165-175 g / eq, bisphenol A diglycidyl ether EMTE127 with an epoxy equivalent of 180-185 g / eq, or bisphenol A diglycidyl ether EMTE128 with an epoxy equivalent of 183-190 g / eq. The epoxy resin used in this invention is one or more of EMTE160, EMTE170L, EMTE170, EMTE126, EMTE127 or EMTE128 produced by Shandong Aimont New Material Co., Ltd., preferably an oily epoxy resin component with high strength formed by epoxy equivalent.
[0014] Preferably, in the oily epoxy resin component, the epoxy curing agent is one or more of the following: phenolic amine curing agents, aliphatic amine curing agents, cycloaliphatic amine curing agents, and modified amine curing agents. More preferably, it is one or more of the following: Evonik 2738 curing agent with an active hydrogen equivalent of 95 g / eq, Evonik 2726 curing agent with an active hydrogen equivalent of 115 g / eq, Evonik 2883 curing agent with an active hydrogen equivalent of 75 g / eq, Evonik 2914UF curing agent with an active hydrogen equivalent of 95 g / eq, Evonik 2636 curing agent with an active hydrogen equivalent of 78 g / eq, or Evonik I-965 curing agent with an active hydrogen equivalent of 102 g / eq. The epoxy curing agent used in this invention is one or more of Evonik 2738 curing agent, Evonik 2726 curing agent, Evonik 2883 curing agent, Evonik 2914UF curing agent, Evonik 2636 curing agent or Evonik I-965 curing agent produced by Evonik Industries.
[0015] Preferably, the diluent is: o-tolyl glycidyl ether with an epoxy equivalent of 200-220 g / eq, benzyl glycidyl ether with an epoxy equivalent of 200-220 g / eq, butyl glycidyl ether with an epoxy equivalent of 130-150 g / eq, carbodole to tetradecyl glycidyl ether with an epoxy equivalent of 310-350 g / eq, ethylene glycol diglycidyl ether with an epoxy equivalent of 100-120 g / eq, 1,4-butanediol diglycidyl ether with an epoxy equivalent of 115-135 g / eq, epoxy... One or more of the following: 1,6-hexanediol diglycidyl ether with an epoxy equivalent of 130-150 g / eq; 1,4-cyclohexanediethanol diglycidyl ether with an epoxy equivalent of 140-160 g / eq; neopentyl glycol diglycidyl ether with an epoxy equivalent of 125-145 g / eq; glycerol triglycidyl ether with an epoxy equivalent of 90-110 g / eq; trimethylolpropane triglycidyl ether with an epoxy equivalent of 95-115 g / eq; or pentaerythritol tetraglycidyl ether with an epoxy equivalent of 75-95 g / eq.
[0016] Preferably, the defoamer is BYK-A530 defoamer.
[0017] A second aspect of the present invention is to provide a method for preparing the above-mentioned waterborne epoxy emulsion modified low linear expansion coefficient repair mortar, comprising the following steps: Preheating: Heat the low-purity crushed molten quartz sand to 50~60℃.
[0018] Preparation of waterborne epoxy emulsion components: The waterborne epoxy emulsion and the waterborne curing agent are stirred evenly in proportion at a stirring speed of 200~400 rpm for 2~5 min, and water is added and stirring is continued for 1~2 min to obtain the waterborne epoxy emulsion components.
[0019] Mixing and spraying: The preheated low-purity crushed fused silica sand is put into a sealed high-speed mixer. The main unit speed is adjusted to 200~400 rpm. Compressed air with a pressure of 0.3~0.5MPa is used to uniformly atomize and spray the water-based epoxy emulsion component into the mixer through an atomizing nozzle. The spraying time is 3~5 minutes, and the ambient temperature is maintained at 50~60℃ throughout the process. The water-based epoxy emulsion component is used to coat the surface of the low-purity crushed fused silica sand particles, so that the surface is uniformly wetted and there is no free emulsion, thus obtaining pre-coated fused silica sand.
[0020] Drying and film formation: After spraying, the pre-coated fused silica sand is continuously stirred and dried by blowing air for 10-15 minutes to promote the dehydration of the water-based epoxy emulsion component on the surface of the pre-coated fused silica sand particles and form a coating film to obtain modified fused silica sand.
[0021] Mortar mixing: The epoxy resin, epoxy diluent, defoamer and epoxy curing agent are mixed evenly according to the formula to prepare an epoxy-based liquid. The modified fused silica sand is added to the epoxy-based liquid and stirred at 200~400 rpm for 2~5 min to obtain the water-based epoxy emulsion modified low linear expansion coefficient repair mortar.
[0022] This invention abandons traditional coupling agent modification and designs a process for pre-coating fused silica sand with waterborne epoxy emulsion. Addressing the issues of surface inertness of fused silica sand after high-temperature preparation, poor modification effect of traditional silane coupling agents (such as KH-550 / KH-560), and poor wetting of oil-based epoxy, this application does not use coupling agents. Instead, it utilizes the low surface tension and strong penetration characteristics of waterborne epoxy emulsion to form a stable coating film on the sand particle surface through "preheating – atomization spraying – drying film formation." The micropores of the silica sand permeate and interlock, and polar dipole adsorption construct a three-dimensional bond, solving the problems of poor cohesion and lack of compactness. The resulting repair mortar has characteristics such as low linear expansion coefficient and high durability, with the linear expansion coefficient reduced to 8~12×10⁻⁶. -6 / ℃, eliminates temperature-dependent interfacial shear stress, improves durability by more than 50% in long-term temperature-dependent environments (such as -25~55℃ thermal cycling, test reference DL / T5193 Appendix G), and has minimal attenuation of bonding strength.
[0023] Secondly, the process of this invention is simple and has strong engineering applicability. The preparation method only requires conventional equipment such as high-speed mixers and atomizing nozzles. The steps are simple and do not require complex chemical bonding treatment. The resulting mortar has high viscosity (it can be formed into a ball when squeezed and does not fall apart when released), high strength (compressive strength ≥85MPa), and excellent impact and abrasion resistance, making it suitable for batch construction of various concrete defect repairs.
[0024] Furthermore, before mixing the mortar, the modified fused silica sand is cooled and sieved using a five-layer square-hole sieve with mesh sizes of 2.5, 1.25, 0.63, 0.315, and 0.16 mm to break up large particles that previously appeared due to slight agglomeration.
[0025] The beneficial effects of this invention are: (1) This invention uses crushed fused silica sand with a purity ≤98%. Compared with conventional electronic-grade high-purity fused silica sand (purity ≥99%, expensive), this low-purity crushed fused silica sand is only 20%~30% of the price of high-purity material. Furthermore, the inherent linear expansion coefficient of this filler is only 0.5×10⁻⁶. -6 / ℃, which is far lower than the linear expansion coefficient of conventional fine aggregates of 10×10. -6 At / ℃, with high-proportion filling, the overall linear expansion coefficient of epoxy mortar can be adjusted to 8~12×10. -6 / ℃, which matches the deformation characteristics of concrete substrate, can effectively eliminate the shear stress at the concrete-epoxy mortar interface caused by temperature changes, and prevent the repair layer from hollowing and falling off under long-term temperature change environment from the root.
[0026] (2) This invention abandons the traditional method of modifying or not modifying with coupling agents. It utilizes the low surface tension and strong penetration characteristics of waterborne epoxy emulsion to penetrate into the micropores of fused silica sand. After curing, it forms micro-mechanical interlocking points. At the same time, the polar groups of waterborne epoxy and the Si-O-Si bonds on the surface of silica sand generate dipole adsorption to construct a three-dimensional coating and bonding structure, which effectively solves the problems of poor wettability of fused silica sand and epoxy system and insufficient cohesiveness of mortar.
[0027] (3) This invention breaks through the bottleneck of conventional additive modification failure. It achieves high-strength bonding between modified aggregate and resin by using water-based epoxy fully coated fused silica sand. The finished mortar has high strength, high toughness and excellent impact and abrasion resistance. Its durability is improved by more than 50% under long-term temperature alternating service environment, achieving both low expansion and high durability. The bonding strength decay is extremely low after cold and hot cycles, reducing the later operation and maintenance costs. At the same time, it uses low-cost, low-purity fused silica sand, which has a simple preparation process, does not require complex equipment, is convenient to construct, and is suitable for batch construction of engineering projects.
[0028] (4) The waterborne epoxy emulsion modified low linear expansion coefficient repair mortar prepared by this invention has a compressive strength of 85~100MPa and a tensile strength of 12~20MPa after 28 days, and a linear expansion coefficient of 8~12×10 -6 / ℃, the bond strength to concrete is 4.5~4.7MPa. 300 cycles of thermal cycling from -25℃ to 55℃ for steel plates (linear expansion coefficient 10.2×10⁻⁶) -6 The bonding strength decreases by only 0-3% at / ℃. Compared to conventional repair mortars, this invention's mortar exhibits superior compressive and tensile mechanical properties, strong abrasion resistance, and can withstand the impact and erosion of high-speed water flow, adapting to the harsh stress conditions of hydraulic flood discharge sections. Simultaneously, the thermal deformation characteristics of this mortar are highly similar to those of the concrete substrate, significantly reducing the difference in linear expansion coefficients between the repair material and the base concrete. This overcomes the inherent defect of excessive thermal expansion in ordinary epoxy mortars and greatly reduces the thermal internal stress generated at the interface during temperature cycling. Furthermore, the material forms a strong interfacial bond with the concrete substrate, effectively inhibiting interface cracking, debonding, and peeling of the repair layer under repeated temperature changes. Compared to conventional repair mortars, this significantly improves the overall long-term service durability and structural reliability of the repair system. Detailed Implementation
[0029] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0030] This invention provides a technical solution: Embodiments of the present invention provide a water-based epoxy emulsion modified low linear expansion coefficient repair mortar, comprising, by weight, 100 parts of low-purity crushed fused silica sand, 2-10 parts of water-based epoxy emulsion component, and 12-20 parts of oil-based epoxy resin component; wherein the low-purity crushed fused silica sand has a silica purity of 90%-98% and a linear expansion coefficient of 0.4-0.6 × 10⁻⁶. -6 / ℃. The surface of the low-purity crushed fused silica sand particles is coated with a coating film formed after the water-based epoxy emulsion component has cured.
[0031] The raw materials of the waterborne epoxy emulsion component include: waterborne epoxy emulsion, waterborne curing agent, and water, wherein the mass ratio of the waterborne epoxy emulsion to the waterborne curing agent is 0.2~5:1, and the water is 0.5~2 times the total amount of the waterborne epoxy emulsion and the waterborne curing agent; the bonding strength of the waterborne epoxy emulsion component to the low-purity crushed fused silica sand is ≥2.0MPa.
[0032] By weight, the oily epoxy resin component comprises: 100 parts epoxy resin, 10-25 parts epoxy diluent, 0.3-0.6 parts defoamer, and 25-100 parts epoxy curing agent.
[0033] The low-purity crushed fused silica sand has a particle size of 0.01mm to 2.5mm, and the sand gradation is as follows: 1.25 to 2.5mm: 5% to 15%, 0.63 to 1.25mm: 20% to 40%, 0.315 to 0.63mm: 20% to 40%, 0.16 to 0.315mm: 10% to 30%, and 0.01 to 0.16mm: 5% to 25%.
[0034] Preferably, the waterborne epoxy emulsion is waterborne epoxy emulsion HB380, and the waterborne curing agent is waterborne curing agent HB6610; the waterborne epoxy emulsion HB380 has a viscosity of 1000~2000cps at 25℃, a solid content of 60wt%, and an epoxy equivalent of 370g / eq; the waterborne curing agent HB6610 has a viscosity of 100~200cps at 25℃, a solid content of 50wt%, an amine value of 220~250mgKOH / g, and an active hydrogen equivalent of 190g / eq.
[0035] Preferably, the epoxy resin is one or more of the following: bisphenol F diglycidyl ether EMTE160 with an epoxy equivalent of 155-165 g / eq, bisphenol F diglycidyl ether EMTE170L with an epoxy equivalent of 165-167 g / eq, bisphenol F diglycidyl ether EMTE170 with an epoxy equivalent of 165-175 g / eq, bisphenol A diglycidyl ether EMTE126 with an epoxy equivalent of 165-175 g / eq, bisphenol A diglycidyl ether EMTE127 with an epoxy equivalent of 180-185 g / eq, or bisphenol A diglycidyl ether EMTE128 with an epoxy equivalent of 183-190 g / eq.
[0036] Preferably, the epoxy curing agent is one or more of the following: Evonik 2738 curing agent with an active hydrogen equivalent of 95 g / eq, Evonik 2726 curing agent with an active hydrogen equivalent of 115 g / eq, Evonik 2883 curing agent with an active hydrogen equivalent of 75 g / eq, Evonik 2914UF curing agent with an active hydrogen equivalent of 95 g / eq, Evonik 2636 curing agent with an active hydrogen equivalent of 78 g / eq, or Evonik I-965 curing agent with an active hydrogen equivalent of 102 g / eq.
[0037] Preferably, the diluent is: o-tolyl glycidyl ether with an epoxy equivalent of 200-220 g / eq, benzyl glycidyl ether with an epoxy equivalent of 200-220 g / eq, butyl glycidyl ether with an epoxy equivalent of 130-150 g / eq, carbodole to tetradecyl glycidyl ether with an epoxy equivalent of 310-350 g / eq, ethylene glycol diglycidyl ether with an epoxy equivalent of 100-120 g / eq, 1,4-butanediol diglycidyl ether with an epoxy equivalent of 115-135 g / eq, and an epoxy equivalent of... A combination of one or more of the following: 1,6-hexanediol diglycidyl ether at 130-150 g / eq; 1,4-cyclohexanediethanol diglycidyl ether at 140-160 g / eq; neopentyl glycol diglycidyl ether at 125-145 g / eq; glycerol triglycidyl ether at 90-110 g / eq; trimethylolpropane triglycidyl ether at 95-115 g / eq; or pentaerythritol tetraglycidyl ether at 75-95 g / eq.
[0038] Preferably, the defoamer is BYK-A530 defoamer.
[0039] This invention also provides a method for preparing the above-mentioned waterborne epoxy emulsion modified low linear expansion coefficient repair mortar, comprising the following steps: S1 Preheating: The low-purity crushed molten quartz sand is heated to 50~60℃.
[0040] S2 Preparation of waterborne epoxy emulsion components: The waterborne epoxy emulsion and the waterborne curing agent are stirred evenly in proportion, with a stirring speed of 200~400 rpm for 2~5 min, and water is added and stirring is continued for 1~2 min to obtain the waterborne epoxy emulsion components.
[0041] S3 Mixing Spray: The preheated low-purity crushed fused silica sand is put into a sealed high-speed mixer. The main unit speed is adjusted to 200~400 rpm. Compressed air with a pressure of 0.3~0.5MPa is used to uniformly atomize and spray the water-based epoxy emulsion component into the mixer through the atomizing nozzle. The spraying time is 3~5 minutes, and the ambient temperature is controlled to be maintained at 50~60℃ throughout the process. The water-based epoxy emulsion component is used to just coat the surface of the low-purity crushed fused silica sand particles without emulsion flow, thus obtaining pre-coated fused silica sand.
[0042] S4 Drying and Film Formation: After spraying, the pre-coated fused silica sand is continuously stirred while being dried by blowing air for 10-15 minutes. This promotes the dehydration of the aqueous epoxy emulsion component on the surface of the pre-coated fused silica sand particles and the formation of a coating film. The fused silica sand is then cooled and sieved using a five-layer square hole sieve with sieve aperture sizes of 2.5, 1.25, 0.63, 0.315, and 0.16 mm to remove large particles that previously appeared due to slight agglomeration, thus obtaining the modified fused silica sand.
[0043] S5 mortar mixing: The epoxy resin, epoxy diluent, defoamer and epoxy curing agent are mixed evenly according to the formula to prepare an epoxy-based liquid. The modified fused silica sand is added to the epoxy-based liquid and stirred at 200~400 rpm for 2~5 min to obtain the water-based epoxy emulsion modified low linear expansion coefficient repair mortar.
[0044] The repair mortar obtained in this embodiment of the invention has a compressive strength of over 85 MPa and a tensile strength of over 12 MPa after 28 days, with a linear expansion coefficient of less than 12 × 10⁻⁶. -6 At a temperature of -25℃ to 55℃, the bond strength to concrete is above 4.5 MPa. After 300 cycles of thermal cycling from -25℃ to 55℃, the bond strength to steel plates (with a linear expansion coefficient of 10.2 × 10⁻⁶) is also tested. -6 The bond strength decreases by only 0-3% at / ℃.
[0045] The present invention will be further described in detail below with reference to specific embodiments. The following embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. All raw materials used in the embodiments are industrial grade.
[0046] Example 1
[0047] The raw material formulation and preparation process of the waterborne epoxy emulsion modified low linear expansion coefficient repair mortar in Example 1 are basically the same as those in the specific implementation method. The specific implementation is as follows: By weight, the raw materials of Example 1 include: 100 parts of low-purity crushed fused silica sand (purchase price: RMB 800-1500 / t, purity: 96.5%, gradation: 10% for 1.25-2.5mm, 30% for 0.63-1.25mm, 30% for 0.315-0.63mm, 20% for 0.16-0.315mm, and 10% for 0.01-0.16mm); waterborne epoxy emulsion components: 3 parts of waterborne epoxy emulsion HB380, 1.5 parts of waterborne curing agent HB6610, and 3 parts of water; oilborne epoxy resin components: 7 parts of bisphenol F diglycidyl ether EMTE160, 1.4 parts of benzyl glycidyl ether, 0.03 parts of BYK-A530 defoamer, and 4.8 parts of Evonik curing agent 2738.
[0048] Preparation method: S1 Preheating: Place the low-purity crushed molten quartz sand in an oven and heat it to 55°C for later use.
[0049] S2 Preparation of waterborne epoxy emulsion components: Add waterborne epoxy emulsion HB380 and waterborne curing agent HB6610 to a container at a mass ratio of 2:1, and stir at 300 rpm for 2.5 min; then add 3 parts of water (1 times the mass of waterborne epoxy emulsion), and continue stirring for 1.5 min to obtain a uniform waterborne epoxy emulsion component.
[0050] S3 Mixing Spray: Preheated low-purity crushed fused silica sand is fed into a sealed high-speed mixer, and the main unit speed is adjusted to 300 rpm. Compressed air at a pressure of 0.4 MPa is used to uniformly atomize and spray the water-based epoxy emulsion components prepared in S2 into the mixer through an atomizing nozzle. The spraying time is 4 minutes, and the ambient temperature is controlled at 55℃ throughout the process.
[0051] S4 Drying and Film Formation: After spraying, maintain the main unit speed at 300 rpm and continuously blow dry for 12 minutes to promote dehydration and cross-linking of the emulsion on the surface of the fused silica sand particles, forming a stable organic coating film. After the sand particles cool to room temperature, they are sieved using a five-layer square-hole sieve with sizes of 2.5, 1.25, 0.63, 0.315, and 0.16 mm to break up slight agglomerations, obtaining modified fused silica sand.
[0052] S5 mortar mixing: Bisphenol F type diglycidyl ether EMTE160, benzyl glycidyl ether, and BYK-A530 defoamer are mixed, and Evonik 2738 curing agent is added. The mixture is stirred evenly to obtain an epoxy resin base liquid. Modified fused silica sand is added to the resin base liquid and stirred at 400 rpm for 4 minutes to finally obtain a homogeneous, highly cohesive epoxy repair mortar, which is the waterborne epoxy emulsion modified low linear expansion coefficient repair mortar of this invention.
[0053] Performance tests were conducted on the obtained waterborne epoxy emulsion-modified low linear expansion coefficient repair mortar: Mortar condition: It can be formed into a ball when squeezed in the hand, but will not crumble when released.
[0054] After the mortar hardens and is cured for 28 days, its compressive strength is 90 MPa, tensile strength is 14 MPa, and impact and abrasion resistance is 600 h / (kg / m). 2 The coefficient of linear expansion is 8.4 × 10⁻⁶. -6 / ℃, the bond strength to concrete is 4.7MPa. 300 cycles of thermal cycling from -25℃ to 55℃ for steel plates (linear expansion coefficient 10.2×10⁻⁶) -6 The bond strength decreased by 2% at / ℃.
[0055] It is understandable that the coefficient of linear expansion of steel plates is similar to that of ordinary concrete (8~12×10). -6 The temperatures (°C) are on the same order of magnitude; if concrete is used directly as the substrate for cyclic testing, the alternating hot and cold temperatures will cause the concrete matrix itself to deteriorate, interfering with the accurate evaluation of the bonding strength of the repair mortar interface. The embodiment of this application uses a steel plate as the carrier for performance evaluation, which can effectively avoid the test interference caused by the deterioration of the concrete matrix itself, making the evaluation results more realistic and reliable.
[0056] Example 2
[0057] The preparation process of the waterborne epoxy emulsion modified low linear expansion coefficient repair mortar in Example 2 is basically the same as that in Example 1, except that, by weight, the total amount of oily epoxy resin component in the raw materials of Example 2 is 21% more than that in Example 1, including: 9 parts of bisphenol F diglycidyl ether EMTE160, 0.9 parts of benzyl glycidyl ether, 0.05 parts of BYK-A530 defoamer, and 6 parts of Evonik 2738 curing agent. The rest of the implementation method is basically the same as that in Example 1.
[0058] Performance tests were conducted on the obtained waterborne epoxy emulsion-modified low linear expansion coefficient repair mortar: Mortar condition: It can be formed into a ball when squeezed in the hand, but will not crumble when released.
[0059] After the mortar hardens and is cured for 28 days, its compressive strength is 99 MPa, tensile strength is 18.1 MPa, and impact abrasion resistance is 688 h / (kg / m²). 2The coefficient of linear expansion is 9.8 × 10⁻⁶. -6 / ℃, the bond strength to concrete is 4.5MPa. 300 cycles of thermal cycling from -25℃ to 55℃ for steel plates (linear expansion coefficient 10.2×10⁻⁶) -6 The bond strength did not decrease at / ℃.
[0060] Example 3
[0061] The preparation process of the waterborne epoxy emulsion modified low linear expansion coefficient repair mortar in Example 3 is basically the same as that in the specific implementation method. The only difference is that, by weight, the total amount of oil-based epoxy resin component in the raw materials of Example 3 is 48% more than that in Example 1, including: 11 parts of bisphenol F diglycidyl ether EMTE160, 1.1 parts of benzyl glycidyl ether, 0.06 parts of BYK-A530, and 7.4 parts of Evonik 2738 curing agent. The rest of the implementation method is basically the same as that in Example 1.
[0062] Performance tests were conducted on the obtained waterborne epoxy emulsion-modified low linear expansion coefficient repair mortar: Mortar condition: It can be formed into a ball when squeezed in the hand, but will not crumble when released.
[0063] After the mortar hardened and cured for 28 days, its compressive strength was 95 MPa, tensile strength was 16.3 MPa, impact and abrasion resistance was 630 h / (kg / m²), and linear expansion coefficient was 11.8 × 10⁻⁶. -6 / ℃, the bond strength to concrete is 4.7MPa. 300 cycles of thermal cycling from -25℃ to 55℃ for steel plates (linear expansion coefficient 10.2×10⁻⁶) -6 The bond strength decreased by 3% at / ℃.
[0064] Example 4
[0065] The preparation process of the waterborne epoxy emulsion modified low linear expansion coefficient repair mortar in Example 4 is basically the same as that in the specific implementation method. The only difference is that the purity of the low-purity crushed fused silica sand used in Example 4 is 90%. The rest of the implementation method is basically the same as that in Example 1.
[0066] Performance tests were conducted on the obtained waterborne epoxy emulsion-modified low linear expansion coefficient repair mortar: Mortar condition: It can be formed into a ball when squeezed in the hand, but will not crumble when released.
[0067] After the mortar hardened and cured for 28 days, its compressive strength was 91 MPa, tensile strength was 15.2 MPa, impact and abrasion resistance was 590 h / (kg / m²), and linear expansion coefficient was 9.2 × 10⁻⁶. -6 / ℃, the bond strength to concrete is 4.6MPa. 300 cycles of thermal cycling from -25℃ to 55℃ for steel plates (linear expansion coefficient 10.2×10⁻⁶) -6 The bond strength decreased by 2% at / ℃.
[0068] Comparative Example 1
[0069] Comparative Example 1 uses common silica sand (linear expansion coefficient 11 × 10⁻⁶) commonly used in this field. -6 The low-purity molten crushed quartz sand of the present invention was not used as the filler ( / ℃), and the other raw materials and preparation methods were basically the same as in Example 1.
[0070] The performance of the obtained repair mortar was tested: Mortar condition: It can be formed into a ball when squeezed in the hand, but will not crumble when released.
[0071] After the mortar hardens and is cured for 28 days, its compressive strength is 92 MPa, tensile strength is 13.5 MPa, and impact abrasion resistance is 610 h / (kg / m). 2 The coefficient of linear expansion is 19.6 × 10⁻⁶. -6 / ℃, the bond strength to concrete is 4.6MPa. 300 cycles of thermal cycling from -25℃ to 55℃ for steel plates (linear expansion coefficient 10.2×10⁻⁶) -6 The bond strength decreases by 55% at / ℃.
[0072] As can be seen from the test results of the examples and Comparative Example 1, the surface of ordinary quartz sand is rich in hydroxyl groups, which can be wetted by oily epoxy. However, the bonding strength of the examples decreased by ≤3% after 300 cold and hot cycles, while that of the comparative example decreased by 55%, and its performance was far inferior to that of the present invention.
[0073] Comparative Example 2
[0074] The implementation method of Comparative Example 2 is basically the same as that of Example 1, except that the low-purity crushed fused silica sand is not surface modified by water-based epoxy emulsion.
[0075] The performance of the obtained repair mortar was tested: Mortar condition: It is not dense when squeezed by hand, and it becomes loose when released.
[0076] After the mortar hardened and cured for 28 days, its compressive strength was 47 MPa, tensile strength was 5.7 MPa, impact and abrasion resistance was 133 h / (kg / m²), and linear expansion coefficient was 8.3 × 10⁻⁶. -6 / ℃, the bond strength to concrete is 4.4MPa. 300 cycles of thermal cycling from -25℃ to 55℃ for steel plates (linear expansion coefficient 10.2×10⁻⁶) -6 The bond strength decreased by 4% at / ℃.
[0077] Comparative Example 3
[0078] The implementation method of Comparative Example 3 is basically the same as that of Example 1, except that the same amount of silane coupling agent KH550 aqueous solution is used to modify the surface of low-purity crushed fused silica sand.
[0079] The performance of the obtained repair mortar was tested: Mortar condition: It is not dense when squeezed by hand, and it becomes loose when released.
[0080] After the mortar hardened and cured for 28 days, its compressive strength was 37 MPa, tensile strength was 3.3 MPa, impact and abrasion resistance was 88 h / (kg / m²), and linear expansion coefficient was 9.3 × 10⁻⁶. -6 / ℃, the bond strength to concrete is 3.8MPa. 300 cycles of thermal cycling from -25℃ to 55℃ for steel plates (linear expansion coefficient 10.2×10⁻⁶) -6 The bond strength decreased by 2% at / ℃.
[0081] After hydrolysis, KH550 coupling agent cannot form chemical bonds due to the lack of silanol groups on the surface of fused silica sand. Instead, it undergoes self-crosslinking and condensation, forming a loose crosslinking layer on the surface of the sand particles. This hinders the direct contact between the epoxy resin and the sand particles, leading to a further decrease in mechanical properties.
[0082] Comparative Example 4
[0083] The implementation method of Comparative Example 4 is basically the same as that of Example 1, except that the same amount of acrylic acid aqueous solution is used to modify the surface of low-purity crushed fused silica sand, and the bonding strength of the acrylic acid solution to the fused silica sand is 0.5 MPa.
[0084] The performance of the obtained repair mortar was tested: Mortar condition: It should feel firm when squeezed in the hand and not crumble when released.
[0085] After the mortar hardens and is cured for 28 days, its compressive strength is 64 MPa, tensile strength is 6.8 MPa, and impact abrasion resistance is 376 h / (kg / m). 2 The coefficient of linear expansion is 9.3 × 10⁻⁶. -6 / ℃, the bond strength to concrete is 4.3MPa. 300 cycles of thermal cycling from -25℃ to 55℃ for steel plates (linear expansion coefficient 10.2×10⁻⁶) -6 The bond strength decreased by 2% at / ℃.
[0086] The above description is merely a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the forms disclosed herein and should not be construed as excluding other embodiments. It can be used in various other combinations, modifications, and environments, and can be altered within the scope of the concept described herein through the above teachings or related technologies or knowledge. Modifications and variations made by those skilled in the art that do not depart from the spirit and scope of the present invention should be within the protection scope of the appended claims.
Claims
1. A water-based epoxy emulsion modified low linear expansion coefficient repair mortar, characterized in that: By weight, the raw materials include: 100 parts of low-purity crushed fused silica sand, 2-10 parts of water-based epoxy emulsion component, and 12-20 parts of oil-based epoxy resin component; the low-purity crushed fused silica sand has a silica purity of 90%-98% and a linear expansion coefficient of 0.4-0.6×10⁻⁶. -6 / ℃; The surface of the low-purity crushed fused silica sand particles is coated with a coating film formed after the water-based epoxy emulsion component has been cured. The raw materials of the waterborne epoxy emulsion component include: waterborne epoxy emulsion, waterborne curing agent, and water. The mass ratio of the waterborne epoxy emulsion to the waterborne curing agent is 0.2~5:1, and the water is 0.5~2 times the total amount of the waterborne epoxy emulsion and the waterborne curing agent. The bonding strength of the waterborne epoxy emulsion component to the low-purity crushed fused silica sand is ≥2.0MPa. By weight, the oily epoxy resin component comprises: 100 parts epoxy resin, 10-25 parts epoxy diluent, 0.3-0.6 parts defoamer, and 25-100 parts epoxy curing agent.
2. The waterborne epoxy emulsion modified low linear expansion coefficient repair mortar according to claim 1, characterized in that: The low-purity crushed fused silica sand has a particle size of 0.01mm to 2.5mm, and the sand gradation is as follows: 1.25 to 2.5mm: 5% to 15%, 0.63 to 1.25mm: 20% to 40%, 0.315 to 0.63mm: 20% to 40%, 0.16 to 0.315mm: 10% to 30%, and 0.01 to 0.16mm: 5% to 25%.
3. The waterborne epoxy emulsion modified low linear expansion coefficient repair mortar according to claim 1, characterized in that: The aqueous epoxy emulsion has a viscosity of 100~2000 cps at 25°C, a solid content of 35~100 wt%, and an epoxy equivalent of 120~400 g / eq; the aqueous curing agent has a viscosity of 100~2000 cps at 25°C, a solid content of 30~100 wt%, an amine value of 120~250 mg KOH / g, and an active hydrogen equivalent of 70~210 g / eq.
4. The waterborne epoxy emulsion modified low linear expansion coefficient repair mortar according to claim 1, characterized in that: In the oily epoxy resin component, the epoxy resin is one or more of the following: bisphenol F diglycidyl ether with an epoxy equivalent of 155-165 g / eq, bisphenol F diglycidyl ether with an epoxy equivalent of 165-167 g / eq, bisphenol F diglycidyl ether with an epoxy equivalent of 165-175 g / eq, bisphenol A diglycidyl ether with an epoxy equivalent of 165-175 g / eq, bisphenol A diglycidyl ether with an epoxy equivalent of 180-185 g / eq, or bisphenol A diglycidyl ether with an epoxy equivalent of 183-190 g / eq.
5. The waterborne epoxy emulsion modified low linear expansion coefficient repair mortar according to claim 1, characterized in that: In the oily epoxy resin component, the epoxy curing agent is one or more of the following: phenolic amine curing agents, aliphatic amine curing agents, cycloaliphatic amine curing agents, and modified amine curing agents.
6. The waterborne epoxy emulsion modified low linear expansion coefficient repair mortar according to claim 1, characterized in that: The diluent is: o-tolyl glycidyl ether with an epoxy equivalent of 200-220 g / eq, benzyl glycidyl ether with an epoxy equivalent of 200-220 g / eq, butyl glycidyl ether with an epoxy equivalent of 130-150 g / eq, carbodole to tetradecyl glycidyl ether with an epoxy equivalent of 310-350 g / eq, ethylene glycol diglycidyl ether with an epoxy equivalent of 100-120 g / eq, 1,4-butanediol diglycidyl ether with an epoxy equivalent of 115-135 g / eq, and epoxy equivalent... One or more of the following: 1,6-hexanediol diglycidyl ether at 130-150 g / eq; 1,4-cyclohexanediethanol diglycidyl ether at 140-160 g / eq; neopentyl glycol diglycidyl ether at 125-145 g / eq; glycerol triglycidyl ether at 90-110 g / eq; trimethylolpropane triglycidyl ether at 95-115 g / eq; or pentaerythritol tetraglycidyl ether at 75-95 g / eq.
7. The method for preparing waterborne epoxy emulsion modified low linear expansion coefficient repair mortar according to any one of claims 1-6, characterized in that: Includes the following steps: Preheating: The low-purity crushed and fused silica sand is heated to 50~60℃; Preparation of waterborne epoxy emulsion components: The waterborne epoxy emulsion and the waterborne curing agent are stirred evenly in proportion, the stirring speed is 200~400 rpm, the stirring time is 2~5 min, water is added and stirring is continued for 1~2 min to obtain the waterborne epoxy emulsion components; Mixing and spraying: The preheated low-purity crushed fused silica sand is put into a sealed high-speed mixer. The main unit speed is adjusted to 200~400 rpm. Compressed air with a pressure of 0.3~0.5MPa is used to uniformly atomize and spray the water-based epoxy emulsion component into the mixer through an atomizing nozzle. The spraying time is 3~5 minutes, and the ambient temperature is maintained at 50~60℃ throughout the process. The water-based epoxy emulsion component is used to coat the surface of the low-purity crushed fused silica sand particles, so that the surface is uniformly wetted and there is no free emulsion, thus obtaining pre-coated fused silica sand. Drying and film formation: After spraying, the pre-coated fused silica sand is continuously stirred and dried by blowing air for 10-15 minutes to promote the dehydration of the waterborne epoxy emulsion component on the surface of the pre-coated fused silica sand particles and form a coating film to obtain modified fused silica sand. Mortar mixing: The epoxy resin, epoxy diluent, defoamer and epoxy curing agent are mixed evenly according to the formula to prepare an epoxy-based liquid. The modified fused silica sand is added to the epoxy-based liquid and stirred at 200~400 rpm for 2~5 min to obtain the water-based epoxy emulsion modified low linear expansion coefficient repair mortar.
8. The method for preparing waterborne epoxy emulsion modified low linear expansion coefficient repair mortar according to claim 7, characterized in that: The waterborne epoxy emulsion-modified low linear expansion coefficient repair mortar can achieve a compressive strength of 85~100MPa and a tensile strength of 12~20MPa after 28 days, with a linear expansion coefficient of 8~12×10⁻⁶. -6 At ℃, the bond strength to concrete is 4.5~4.7MPa.
9. The method for preparing waterborne epoxy emulsion modified low linear expansion coefficient repair mortar according to claim 7, characterized in that: Before mixing the mortar, the process also includes: cooling and sieving the modified fused silica sand to break up large particles that previously appeared due to slight agglomeration.
10. The method for preparing waterborne epoxy emulsion modified low linear expansion coefficient repair mortar according to claim 9, characterized in that: The sieving process uses a five-layer square hole sieve with sieve aperture sizes of 2.5, 1.25, 0.63, 0.315, and 0.16 mm.
Citation Information
Patent Citations
Underfill with low viscosity and low linear expansion coefficient
CN101864147A
Epoxy molding composition for surface mount applications
US5434199A